I have a feeling that the following inequality should be very easy to prove:

$$ x^n \geq \prod_{i=1}^n{(x+k_i)},\quad\text{where } \sum_{i=1}^{n}{k_i}=0,\quad \text{and } x+k_i>0\text{ for all } i $$

(and the equality only holds when all the $k_i=0$).

It seems intuitively obvious (when $n=2$, a square has a greater area than a rectangle with the same perimeter, when $n=3$, a cube has greater volume than a rectangular prism with the same surface area, etc.) but I can't find an appropriately easy proof.

I think I can show it analytically by finding the local maximum for $f(x_1,\ldots,x_n)=\prod_{i=1}^n{x_i}$ within the box $\max{x_i}=r$ in the upper-right quadrant, but I feel like there should be a neat algebraic/geometric argument, since it's such an intuitive statement.

  • $\begingroup$ What do we assume on $k_i$ and $x$? Non negative? $\endgroup$ – Davide Giraudo Dec 25 '11 at 23:36
  • $\begingroup$ Sure nonnegativity for $x$, otherwise $n=2,x=-1,k_1=1,k_2=-1$ provides a counterexample. But we can't require that $k_i$ be nonnegative, as this would only allow the trivial case $k_i=0,\forall i$. $\endgroup$ – Alex Becker Dec 25 '11 at 23:39
  • $\begingroup$ Edited to clarify that $x>0$. Of course, as Alex says, the $k_i$ can be negative. $\endgroup$ – Adrian Petrescu Dec 25 '11 at 23:44
  • $\begingroup$ Actually, now that I think a bit more about it, it may also be necessary to require that $x+k_i>0$ for all $i$, but I'm not 100% sure. Hopefully someone will point this out. Thinking more about it... $\endgroup$ – Adrian Petrescu Dec 25 '11 at 23:49
  • $\begingroup$ You need some restrictions on the $k_i$: $2^3< (2-4)(2-4)(2+8)$. $\endgroup$ – David Mitra Dec 25 '11 at 23:49

The AM-GM inequality gives us $$\prod_i (x+k_i)^{1/n} \leq {1\over n}\sum_i (x+k_i)=x.$$ Now take the $n$th power of both sides.

  • $\begingroup$ I was gonna say: take the logs and apply Jensen, but realized that is the same solution :) $\endgroup$ – N. S. Dec 26 '11 at 1:38
  • $\begingroup$ Wow, can't believe I missed that. Thanks! $\endgroup$ – Adrian Petrescu Dec 26 '11 at 1:42
  • $\begingroup$ Yeah, I used the log function in my first solution, but I thought this was cleaner. $\endgroup$ – user940 Dec 26 '11 at 1:43

We can show it by induction: for $n=2$, we have for $a+b=0$: $x^2-(x+a)(x+b)=-(a+b)x-ab=-ab\geq 0$, since $ab\leq 0$. We assume that the result is true for $n$. Let $(k_1,\ldots,k_{n+1})$ such that $\sum_{j=1}^{n+1}k_j=0$. We can assume that $k_nk_{n+1}\leq 0$. We put $k_j'=k_j$ if $j\leq n-1$, and $k_n'=k_n+k_{n+1}$. We get by induction hypothesis $$x^n\geq \prod_{j=1}^n(x+k_j')=(x+k_n+k_{n+1})\prod_{j=1}^{n-1}(x+k_j),$$ so $$x^{n+1}\geq x(x+k_n+k_{n+1})\prod_{j=1}^{n-1}(x+k_j),$$ and we have to show that $x(x+k_n+k_{n+1})\geq (x+k_n)(x+k_{n+1})$, since $\prod_{j=1}^{n-1}(x+k_j)\geq 0$. But \begin{align*} x(x+k_n+k_{n+1})-(x+k_n)(x+k_{n+1})&=x(k_n+k_{n+1})-xk_{n+1}-xk_n-k_nk_{n+1}\\ &=-k_nk_{n+1}\geq 0. \end{align*}

  • $\begingroup$ Ah, I see it! Thanks for this :) $\endgroup$ – Adrian Petrescu Dec 26 '11 at 0:12

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.